Dukungan Sosial Bagi Pasien Kanker Payudara di Rumah Singgah Humanis Kota Bandung - Nabila Rifatunnafiah; Gigin Ginanjar Kamil Basar; Hery Wibowo (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
This study examines social support for breast cancer patients at the Humanis Shelter in Bandung City with a focus on four forms of support according to Sarafino & Smith (2011): emotional, appreciation, instrumental and informational support. This study describes the role of the shelter in providing social support using qualitative methods with a phenomenological approach. The purpose of this study was to describe the four forms of social support provided and their impact on patients. Data collection was carried out through in-depth interviews with administrators and patients at the shelter, participatory observation and secondary data conducted from March to June 2025. The results of the study indicate that social support has been provided comprehensively, namely emotional support is provided through counseling and religious activities; appreciation support in the form of verbal appreciation and recreation; instrumental support includes logistical and administrative services, while information support is delivered through social media and counseling activities. These findings reinforce the importance of integrating social support into shelter services to improve the quality of life of patients. The weaknesses found lie in the suboptimal structured counseling and routine recreational activities. This study provides suggestions for further examining the effectiveness of each form of support and comparisons between shelters in providing social support. Keywords: Social Support, Breast Cancer, Shelter Home